The principle against confiscation and tax fines in current jurisprudence of the STF (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This paper deals with the parameters used by the case law of the Federal Supreme Court when analyzing the application of the principle of prohibition of confiscation to tax fines. The study also addresses the main aspects surrounding the provision of this principle in the 1988 Constitution, as well as its relationship with tax penalties.
Keywords: tax; confiscation; fines; sanctions; jurisprudence; STF